Effect of liraglutide on body weight and pain in patients with overweight and knee osteoarthritis: protocol for a randomised, double-blind, placebo-controlled, parallel-group, single-centre trial. Issue 5 (5th May 2019) - Gudbergsen, Henrik; Henriksen, Marius; Wæhrens, Eva Ejlersen; Overgaard, Anders; Bliddal, Henning; Christensen, Robin; Boesen, Mikael Ploug; Knop, Filip Krag; Astrup, Arne; Rasmussen, Marianne Uggen; Bartholdy, Cecilie; Daugaard, Cecilie; et al.
Abstract : Introduction: With an increasing prevalence of citizens of older age and with overweight, the health issues related to knee osteoarthritis (OA) will intensify. Weight loss is considered a primary management strategy in patients with concomitant overweight and knee OA. However, there are no widely available and feasible methods to sustain weight loss in patients with overweight and knee OA. The present protocol describes a randomised controlled trial evaluating the efficacy and safety of the glucagon-like peptide-1 receptor agonist liraglutide in a 3 mg/day dosing in patients with overweight and knee OA. Methods and analysis: 150 volunteer adult patients with overweight or obesity and knee OA will participate in a randomised, double-blind, placebo-controlled, parallel-group and single-centre trial. The participants will partake in a run-in diet intervention phase (week −8 to 0) including a low calorie diet and dietetic counselling. At week 0, patients will be randomised to either liraglutide 3 mg/day or liraglutide placebo 3 mg/day for 52 weeks as an add-on to dietetic guidance on re-introducing regular foods and a focus on continued motivation to engage in a healthy lifestyle. The co-primary outcomes are changes in body weight and the Knee Injury and Osteoarthritis Outcome Score pain subscale from week 0 to week 52. Ethics and dissemination: The trial has been approved by the regional ethics committee in the Capital Region of Denmark, the Danish Medicines Agency and the Danish Data Protection Agency. An external monitoring committee (The Good Clinical Practice Unit at Copenhagen University Hospitals) will oversee the trial. The results will be presented at international scientific meetings and through publications in peer-reviewed journals. Trial registration numbers: 2015-005163-16, NCT02905864, U1111-1171-4970 Based on protocol version: V.6; 30 January 2017, 15:30 hours